Effect of bariatric surgery on employment status—a 7 years controlled nationwide registry study. Issue 6 (22nd June 2021) - Juhl, Claus Bogh; Holst, René; Mundbjerg, Lene Hymøller; Stolberg, Charlotte; Gran, Jon Michael; Thomsen, Gert Frank
Abstract : Background: Severe obesity is associated with a reduced ability to work. Bariatric surgery is the most effective method to achieve a sustained weight loss. Previous studies have reported conflicting results regarding the effect of bariatric surgery on employment status. To address this, we investigated the effect of bariatric surgery on employment status in the Danish population. Methods: In this nationwide study, we identified 5450 subjects who underwent bariatric surgery and 10 900 control subjects matched for age, sex and municipality. From accessible registries, we extracted data regarding employment, absenteeism, sick leave and pension. Using a multistate model, we compared time in occupational states and transitions between these states to determine the effect of bariatric surgery on employment status. Findings: Before surgery, cases had an absolute risk increase (95% CI)(ARI (CI)) and a relative risk (RR (CI)) of being in full-time employment of −0.12 (−0.14 to −0.10) and 0.84 (0.82 to 0.86) and were more often unemployed or in a subsidised job than the background population. Taking into account the employment status before surgery, the bariatric surgery group increased their probability of being in full-time employment 1–3 years after bariatric surgery. However, this positive effect was not present with a longer duration of follow-up. Being male, above 50 years of age, or employed as a craftsman or office worker were associated with a sustained positive effect of being in full-time employment (ARI (CI) and RR (CI) 0.05 (0.04 to 0.05) and 1.05 (1.04 to 1.06), 0.06 (0.06 to 0.07) and 1.08 (1.07 to 1.09) and 0.05 (0.05 to 0.06) and 1.05 (1.05 to 1.06), respectively). Interpretation: Compared with a matched control group, those undergoing bariatric surgery did not improve their employment status in the long term. Certain subgroups had a more sustained positive effect.